Analisis Batuan pada Tanah Beruap dan Tanah Hangat menggunakan SEM-EDX dan FTIR di Desa Tondangow Tomohon - Donny R. Wenas; Satyano Mongan; Waren Cristoper Anthe (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2022)
The island of Sulawesi and its surroundings regionally shows a complex geological structure with mineral complexity due to the accumulation of collisions from various Australian and Pacific macro plates. North Sulawesi Province is one of the areas that have alteration rocks that are commonly found in geothermal manifestation areas. The purpose of this study was to determine the element composition and types of rock minerals in steaming ground and warm ground in Tondangow, North Sulawesi Province. The method used is the electron beam method on SEM, and the energy dispersive X-ray spectroscopic method and FTIR spectroscopy. The results obtained indicate that the composition of rock elements in the steaming ground in Tondangow Village, Tomohon, North Sulawesi Province is O, Si, and Al with the percentage content of O 51.96 percent, Si 40.37 percent, and Al 7.67 percent. For warm ground rocks obtained O and Si content, with the percentage of O 54.40 percent and Si 45.60 percent. The type of rock mineral in the steaming ground is obtained by quartz and kaolinite minerals, which are dominated by quartz. For rocks on warm ground obtained the type of mineral quartz